First data on the diet of Razorbill Alca torda wintering in the Mediterranean Sea: insights from social media - MONTI, FLAVIO; MORI, EMILIANO; BALESTRIERI, ROSARIO; MINICHINO, ADRIANO; VENTO, ROBERTO; VIVIANO, ANDREA; TIRALONGO, FRANCESCO (Mediterranean Marine Science, 2024)
Understanding a species’ diet is of paramount importance to ecology as it provides vital insights into interactions between organisms and their environment. In this study, we report the first data on the diet of wintering Razorbills (Alca torda) in the Mediterranean Sea. Taking advantage of the irruption event that occurred in the Mediterranean in winter 2022/2023, a data mining search campaign was carried out on social media to collect photographs and videos documenting Razorbills feeding at sea. Additional information was gathered by analysing the stomach contents of dead individuals salvaged from the coastline of central Italy. Overall, we obtained records from 32 pictures and 7 videos as well as 7 dead individuals. All prey items belonged to class Actinopterygii. Overall, 12 fish prey were identified (2 at the family, 3 at the genus and 7 at the species level). Razorbills fed on small-medium sized fish species of the neritic zone such as Belone belone, Trachinotus ovatus, Atherina hepsetus and Engraulis encrasicolus. Razorbills were mostly observed foraging close to the coast and within harbours, as well as begging for food from humans, raising doubts about the feeding conditions encountered and the health status of individuals. Dead individuals mainly had empty stomachs, in line with the low weights and fat scores detected during necropsy. We underline how data from social media have made it possible to describe, using non destructive methods, the behaviour and feeding habits of an uncommon seabird typical of the North Atlantic Sea, which caught the attention of photographers, nature enthusiasts, and scientists.